Juvenile Delinquency in Bangladesh: The Impact of Familial and Economic Factors in Dhaka City - Md. Zahidul Islam; Shammi Akter; Md. Sobur Hossain; Nishat Tasnim (Journal of Indonesian Economic Research, 2024)
This study explored the impact of familial and economic factors on juvenile delinquency in Dhaka City, Bangladesh. This study employed a quantitative research design. A survey was executed in designated regions of Dhaka, including Mohammadpur, Mirpur, and Azimpur, including 100 teenagers aged 10 to 18. Data were obtained from this survey. The findings revealed that 80% of teenagers claimed inadequate parental supervision, while 96% had financial difficulties throughout their early childhood. These elements are substantial contributors to criminal activity. Behavior was seen as substantially affected by peer influence (64%) and limited educational access (52%). The results demonstrate that the following types of juvenile delinquency are widespread: Seventy-two (72%) percent of individuals confessed to theft, while fifty-six percent (56%) recognized their participation in vandalism or unlawful alcohol use.  The findings indicated that comprehensive policy interventions and focused community actions mitigate the primary contributing factors to juvenile delinquency in Bangladesh. Improving mental health services, enhancing family support networks, and increasing access to excellent education are essential to alleviate the effects of economic hardship and dysfunctional family dynamics.